2021
DOI: 10.3390/jcm10163509
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Cosmetic Outcome after Reconstruction of Isolated, Unilateral Orbital Floor Fractures (Blow-Out Fractures) with and without the Support of 3D-Printed Orbital Anatomical Models

Abstract: The present study aimed to analyze if a preformed “hybrid” patient-specific orbital mesh provides a more accurate reconstruction of the orbital floor and a better functional outcome than a standardized, intraoperatively adapted titanium implant. Thirty patients who had undergone surgical reconstruction for isolated, unilateral orbital floor fractures between May 2016 and November 2018 were included in this study. Of these patients, 13 were treated conventionally by intraoperative adjustment of a standardized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…Although the surgical options for orbital fractures are still controversially discussed, it is known that a high rate of postoperative complications is still found today 1. A retrospective review analyzed 1594 patients between 2007 and 2017 and found a complication rate of 18%, which is within the range found in the literature in general 1,2. These data highlight the need to implement techniques to improve patient planning and treatment.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Although the surgical options for orbital fractures are still controversially discussed, it is known that a high rate of postoperative complications is still found today 1. A retrospective review analyzed 1594 patients between 2007 and 2017 and found a complication rate of 18%, which is within the range found in the literature in general 1,2. These data highlight the need to implement techniques to improve patient planning and treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Orbital blow-out fractures occur when there is herniation of the infraorbital fat into the maxillary sinus or the region of the ethmoid cells due to the collapse of the floor or medial wall of the orbit 1. Such defects usually generate ophthalmoplegia, enophthalmia, dystopia, and diplopia; therefore, they require a thorough and assertive surgical repair to reconstruct the orbital anatomy 1,2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly concerning accuracy during orbital reconstruction, computer-assisted surgery with preoperative planning helps to guide surgeons during surgery [ 24 ]. Furthermore, pre-bent implants using 3D-printed orbital anatomical models have been shown to provide a more accurate reconstruction of the orbital floor and a better functional outcome than a standardized, intraoperatively adapted titanium implant [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Virtual planning of surgical interventions and implant preparation enhances the confidence of the surgeon, reduces time in the operating room and can improve the functional outcome [ 1 ]. Since the first description of its use in corrective osteotomies of the distal radius in the late 1980s, three-dimensional (3D) virtual surgical planning (VSP) has become popular, particularly with the introduction of certified medical surgical planning software (Mimics, Materialise, Leuven, Belgium; Rhino Medical, Rhino Medical Services, Arlington, Texas, USA) [ 2 – 5 ].…”
Section: Introductionmentioning
confidence: 99%